REVIEW: EFFECTS OF LEADERSHIP STYLES ON QUALITY OF SERVICES IN HEALTHCARE - Alloubani, AlaDeen Mah’d; Almatari, Mohammad; Almukhtar, Mohammad Musa (European Scientific Journal, ESJ, 2014)
Background :There are progressive changes in the work of hospital leaders, included descriptions of how hospital leader work is perceived in a global context. Hospital leaders have had to respond to new technology, new organizational goals and new challenges. The most effective leaders have responded to the dynamism of the healthcare field by altering their leading skill set. Aim: To understand the nature of leadership work of the hospital managers in order to examine their perceptions of the most essential roles, skills and training courses as hospital managers. Also to identify the challenges, obstacles and problems facing hospital leaders. Methods : Hospital leaders were compared to more traditional leaders, highlighting important, yet subtle differences between them. Studies appropriate for inclusion were randomized controlled trials studying the effectiveness of leadership styles among hospital leaders, head nurse managers and healthcare workers. An integrative review of studies from ProQuest, PubMed and Emerald databases was undertaken to explore and analyses studies about leaders and leadership and its effects on outcome. Keywords and phrases used were: Nursing leaders, head nurse manager, nursing leadership, health leader, health leadership, leader functions, leader roles, hospital, healthcare system, job motivation, health policy, qualification needs, professional development, and challenges facing hospital leaders. Findings: Several research studies in the field of leadership found that transformational leadership attributes and behaviours were positively related to organizational outcomes such as teamwork success, effectiveness, staff satisfaction, commitment and extra effort and more. Moreover, transformational leadership processes have been found to enhance followers’ work-oriented values and shape self-efficiencies of followers.Conclusion: According to literature incorporated in this review it can be concluded that effective leadership is one of the most crucial factors that lead an organization towards success. Nowadays the key challenge for modern organization is to recognize the effects of strong leadership upon the nursing performance and success of the organization. Implication for Nursing and health policy: A proficient leader leads nurses and provides direction for an organization towards accomplishing desired goals. The advantages of leadership effectiveness should be stated for nursing administrative and healthcare policy makers.